Performance and Mechanism of U(Ⅵ) Removal by Tricalcium Phosphate - ZHAO Kai-xin; GAO Qiong; TIAN Qiang; YAN Min-hao; HUANG Yi (He huaxue yu fangshe huaxue, 2023)
In order to explore the adsorption performance and mechanism of tricalcium phosphate for removing the U（Ⅵ）, the tricalcium phosphate powder was synthesized by the solid phase method using calcium carbonate and diammonium hydrogen phosphate as the raw materials. And then, the physical and chemical properties of tricalcium phosphate powder were characterized by X-ray diffraction（XRD）, Fourier transform infrared spectroscopy（FTIR）, scanning electron microscopy（SEM） and specific surface area analyzer（Brunauer-Emmett-Teller, BET). The effects of pH, solid-liquid ratio, adsorption time, initial U（Ⅵ） concentration, adsorption temperature on the U（Ⅵ） adsorption performance of tricalcium phosphate were also investigated. The kinetic adsorption, isothermal adsorption, thermodynamic adsorption models, as well as XRD, FTIR, X-ray photoelectron spectroscopy（XPS）, SEM, energy dispersive spectroscopy（EDS）, inductively coupled plasma optical emission spectrometer（ICP-OES） were used to reveal the U（Ⅵ） adsorption mechanism of tricalcium phosphate. The results show that the adsorption capacity of U（Ⅵ） by tricalcium phosphate is up to 999.25 mg/g, when the adsorption conditions are as follows: pH of 3.0, solid-liquid ratio of 0.1 g/L, adsorption time of 60 min, initial U（Ⅵ） mass concentration of 120 mg/L and adsorption temperature of 308 K. The adsorption process conforms to the pseudo-second-order kinetic model(chemical adsorption) and Langmuir model(monolayer adsorption), which is a spontaneous endothermic process. The U（Ⅵ） adsorption mechanism of tricalcium phosphate is the dissolution and precipitation process. In acidic aqueous solution, Ca2+ and PO3-4 dissolved from tricalcium phosphate can combine with UO2+2 to form meta-autunite (Ca(UO2)2-(PO4)2·6H2O) on the surface of tricalcium phosphate. The aforementioned results suggest that tricalcium phosphate can be utilized as a kind of promising adsorption materials for U（Ⅵ） containing wastewater treatment.